A retrospective observational analysis of post-pandemic influenza-related outcomes in the United Kingdom, 2010-2014 - Sankarasubramanian Rajaram; Witold Wiecek; Richard Lawson; Betina Blak; Yanli Zhao; Judith Hackett; Robert Brody; Tehseen Salimi; Billy Amzal; Vishal Patel (Taylor & Francis Group, 2018)
This study set out to evaluate influenza- and respiratory-related illnesses recorded during primary care physician consultations in England following the H1N1 pandemic in 2009 and to enable the development of a dynamic disease model. Data were obtained from the Clinical Practice Research Datalink of primary care records over four influenza seasons (2010-2014). The primary outcome of the study was incidence of influenza- and respiratory-related diagnoses, calculated per practice and by season and age group. Upper respiratory tract infection diagnoses were most frequently recorded (mean seasonal practice level incidence; 3,762 consultations per 100,000 [SD = 1,989]), and influenza-related diagnoses were least frequently recorded across all seasons, except one. Incidence rates for the under 18 population were higher than those for the general population, in particular for upper respiratory tract infection (range of 8,024-9,950 versus 3,228-4,120, respectively) and otitis media diagnoses (2,668-3,652 versus 782-1,057, respectively). For influenza-related diagnoses, the 65+ age group, the 0 to <2 and 2 to <4 groups had a higher risk (risk ratio = 1.33, 1.12 and 1.16, respectively) than other age groups. This study provides valuable insight into the incidence of influenza- and respiratory-related diagnoses in the primary care setting in England, and suggests a higher burden of disease in young children and the elderly. The study also indicates that some influenza illness is likely to be reported under respiratory-related diagnoses, given the low incidence of influenza-related diagnoses in the study.